Out-Group Animus and Punitiveness in Latin America. (July 2020) - Lehmann, Peter S.; Chouhy, Cecilia; Singer, Alexa J.; Stevens, Jessica N.; Gertz, Marc
The social threat perspective anticipates that members of racial/ethnic out-groups might be perceived as socially, politically, or economically threatening; criminally inclined; and in need of social control via the criminal justice system. In light of this framework, the current study examines the influence of out-group animus on punitive sentiments in the rarely explored context of Latin America. Data from the 2012 AmericasBarometer survey collected in nine countries ( N = 15, 145) are analyzed, and the findings indicate that animus against foreigners, Blacks, and the Indigenous is positively associated with support for punitive measures. These results lend support for the social threat perspective and provide further evidence that this relationship might be a cultural universal in societies characterized by racial/ethnic conflict.